The Paradigm of Philosophical Poetics - Kačerauskas, Tomas (Problemos, 2004)
The author of the article asks: what is philosophical poetics; what branches of philosophy stands next to it; what are the paradigms of it? Philosophical poetics is understood here as a philosophical approach without being only the subsidiary mean to expose the philosophical ideas. The openness, the intentionality, the creativeness are the features of the philosophical poetics. As an integral philosophical view it can provide a model for hermeneutics or culture. On the other hand, philosophical poetics is investigated with the help of these philosophical branches, i.e., going the “long way”. Philosophical poetics is based on the presumption that poetry and philosophy stand next to each other. The common foundation of the both is metaphor. The metaphor as a vehicle of poetical language has not only poetical but also the ethical and ontological aspects, that are his “seeing as“, i.e., his extra-linguistic level. So metaphor can be investigated as a paradigm of philosophical poetics. philosophical poetics, metaphor, hermeneutics, phenomenology